ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PADA PERUSAHAHAAN SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI - Nanda Dini Pratiwi; Nurjanti Takarini (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
The purpose of this study was to determine and analyze the effect of Liquidity (Quick Ratio), Total Asset Turnover, and Company Size (Size) on Profitability as measured by Return On Assets either simultaneously or partially. The population in this study are all food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2020. The sample selection was carried out using a non-probability sampling method with purposive sampling technique in order to obtain as many as 22 companies. The type of data used in this study is secondary data, in the form of financial statement data sourced from the Indonesia Stock Exchange. The test method to see the effect of the independent variable on the dependent variable is the multiple linear regression analysis method. Based on the results of the study simultaneously, it is known that QR, TATO and SIZE have a effect on the profitability of manufacturing companies in the food and beverage sub-sector for the 2017-2020 period. However, partially, QR and SIZE have an effect on the company's profitability (ROA), while TATO has no effect on profitability (ROA).